Feszültségek az egyetemi templom építése körül 1938-ban - Kerepeszki, Róbert (Gerundium, 2011)
Tensions Involving the Construction of the University Church in 1938. Next to the Main Building of the University of Debrecen stands a Protestant church which for long years in the past accommodated the periodical holdings of the university’s Main Library. However, by now much of the church’s early history has been forgotten. The study demonstrates that the university’s management supported the view, as early as the very beginning of the 1920s, that for a fundamentally Protestant institution of higher education the government authorities should provide a church of its own. This project was delayed by the world economic crisis of 1929 and the fact that the construction of the Main Building itself of the university was not completed until 1932/1933. The management of the university, the Protestant Diocese of the Trans-Tisza District and the Ministry of Religion and Public Education jointly invited tenders for the construction of the building, the winner of which was a contructor of Jewish background. This decision—reflecting the spirit of the age—elicited aversion from right-wing student organizations. Through presenting the standpoints concerning this event, the study provides a graphic description of the relevant contemporaneous attitudes.